Turistična destinacija Artiče: študija izvedljivosti (University of Maribor Press, 2021)
Tourist Destination Artiče: a Feasibility Study. The book "Tourist destination Artiče: a feasibility study" presents the tourist development perspectives of a potential destination Artiče. Artiče is a place located in the municipality of Brežice in the Posavje region, where recently they have been placing great emphasis on the development of tourism. The municipality is known mainly for spa tourism, but other offerings are also developing – from natural and cultural sights to gastronomic and sports offers. The locals of Artiče, who are proud of their area’s givenness, want to attract visitors to their ends. Hence, they contacted the Faculty of Tourism of the University of Maribor to prepare a feasibility study for a potential tourist destination. Together with the mentors, the students of the 1st year of the master’s program and the 3rd year of the higher education study program participated in the project with the local population’s participation. After analysing the area, they prepared a strategic document for the development of the tourist destination and the marketing plan of individual proposed tourist products.